Effects of vitamin B12 supplementation on neurodevelopment and growth in Nepalese Infants: A randomized controlled trial - Strand, Tor A.; Ulak, Manjeswori; Hysing, Mari; Ranjitkar, Suman; Kvestad, Ingrid; Shrestha, Merina; Ueland, Per M.; McCann, Adrian; Shrestha, Prakash S.; Shrestha, Laxman S.; Chandyo, Ram K. (PLOS Medicine, 2020)
Background Vitamin B12 deficiency is common and affects cell division and differentiation, erythropoiesis, and the central nervous system. Several observational studies have demonstrated associations between biomarkers of vitamin B12 status with growth, neurodevelopment, and anemia. The objective of this study was to measure the effects of daily supplementation of vitamin B12 for 1 year on neurodevelopment, growth, and hemoglobin concentration in infants at risk of deficiency. Methods and findings This is a community-based, individually randomized, double-blind placebo-controlled trial conducted in low- to middle-income neighborhoods in Bhaktapur, Nepal. We enrolled 600 marginally stunted, 6- to 11-month-old infants between April 2015 and February 2017. Children were randomized in a 1:1 ratio to 2 μg of vitamin B12, corresponding to approximately 2 to 3 recommended daily allowances (RDAs) or a placebo daily for 12 months. Both groups were also given 15 other vitamins and minerals at around 1 RDA. The primary outcomes were neurodevelopment measured by the Bayley Scales of Infant and Toddler Development 3rd ed. (Bayley-III), attained growth, and hemoglobin concentration. Secondary outcomes included the metabolic response measured by plasma total homocysteine (tHcy) and methylmalonic acid (MMA). A total of 16 children (2.7%) in the vitamin B12 group and 10 children (1.7%) in the placebo group were lost to follow-up. Of note, 94% of the scheduled daily doses of vitamin B12 or placebo were reported to have been consumed (in part or completely). In this study, we observed that there were no effects of the intervention on the Bayley-III scores, growth, or hemoglobin concentration. Children in both groups grew on an average 12.5 cm (SD: 1.8), and the mean difference was 0.20 cm (95% confidence interval (CI): −0.23 to 0.63, P = 0.354). Furthermore, at the end of the study, the mean difference in hemoglobin concentration was 0.02 g/dL (95% CI: −1.33 to 1.37, P = 0.978), and the difference in the cognitive scaled scores was 0.16 (95% CI: −0.54 to 0.87, P = 0.648). The tHcy and MMA concentrations were 23% (95% CI: 17 to 30, P < 0.001) and 30% (95% CI: 15 to 46, P < 0.001) higher in the placebo group than in the vitamin B12 group, respectively. We observed 43 adverse events in 36 children, and these events were not associated with the intervention. In addition, 20 in the vitamin B12 group and 16 in the placebo group were hospitalized during the supplementation period. Important limitations of the study are that the strict inclusion criteria could limit the external validity and that the period of vitamin B12 supplementation might not have covered a critical window for infant growth or brain development. Conclusions In this study, we observed that vitamin B12 supplementation in young children at risk of vitamin B12 deficiency resulted in an improved metabolic response but did not affect neurodevelopment, growth, or hemoglobin concentration. Our results do not support widespread vitamin B12 supplementation in marginalized infants from low-income countries. Trial registration ClinicalTrials.gov NCT02272842 Universal Trial Number: U1111-1161-5187 (September 8, 2014) Trial Protocol: Original trial protocol: PMID: 28431557 (reference [18]; study protocols and plan of analysis included as Supporting information).